Simulation of iron oxide/silica precipitation in the paragoethite process for the removal of iron from acidic zinc leach solutions - Dyer, L.; Richmond, William; Fawell, Phillip (Elsevier Science BV, 2012)
An investigation of the simultaneous precipitation of iron oxide and silica species from acidic solutions was conducted, simulating the Paragoethite Process, an iron-removal stage employed in zinc hydrometallurgy. Laboratory-based continuous crystallisation experiments were carried under the primary conditions employed in industry, with pH (at 85°C) maintained at 2.65, the combined Fe and Si concentration at 0.1128 M (unless otherwise stated) and Si:Fe ratios varied from 0 to 0.43. The crystal structure of the residues produced was characterised, with the extent of iron and silicate removal quantified and properties relating to aggregate structure also measured. It is shown that the degree of silica polymerisation prior to the precipitation reaction dictates the mechanism of co-precipitation and thereby the properties of the residue. In the presence of polymerised silica, less dense aggregates of finer mean particle size are formed, which has negative implications for dewatering. Conversely, where silica is allowed to polymerise prior to the iron precipitation reaction, a greater proportion of silica is removed from solution. Close control of silica polymerisation in the feed liquor is therefore required to reach a compromise between its beneficial and detrimental influences, and to thereby obtain optimal performance.